1999
DOI: 10.1111/j.1600-065x.1999.tb01360.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteases involved in MHC dass II antigen presentation

Abstract: Summary: Major histocompatibility complex class II antigen presentation requires the participation of lysosomal proteases in two convergent processes. First, the antigens endocytosed by the antigen‐presenting cells must be broken down into antigenic peptides. Second, class II tnolecules are synthesized with their peptide‐binding site blocked by invariant chain (li), and they acquire the capacity to bind antigens only after Ii has been degraded in the compartments where peptides reside. The study of geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
121
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(124 citation statements)
references
References 72 publications
1
121
0
2
Order By: Relevance
“…Functional class II expression is highly dependent on the expression of two main chaperones, the invariant chain (Ii) and DM. Newly synthesized class II ␣-and ␤-chains form a nonameric complex with three Ii molecules in the endoplasmic reticulum (ER) (9) where Ii blocks the peptidebinding groove (10) and guides class II dimers to the endocytic pathway where Ii is proteolytically cleaved leaving the CLIP fragment bound to class II (11). Peptide loading and editing mainly occurs in late endocytic compartments designated MHC II-containing compartments (12).…”
mentioning
confidence: 99%
“…Functional class II expression is highly dependent on the expression of two main chaperones, the invariant chain (Ii) and DM. Newly synthesized class II ␣-and ␤-chains form a nonameric complex with three Ii molecules in the endoplasmic reticulum (ER) (9) where Ii blocks the peptidebinding groove (10) and guides class II dimers to the endocytic pathway where Ii is proteolytically cleaved leaving the CLIP fragment bound to class II (11). Peptide loading and editing mainly occurs in late endocytic compartments designated MHC II-containing compartments (12).…”
mentioning
confidence: 99%
“…Antigen processing consists of protein denaturation and fragmentation. Several proteases have been described to be part of this system (17). Proteins that contain disulfide bonds require an additional processing step, the reduction of the cysteine residues to produce antigenic peptides (18).…”
mentioning
confidence: 99%
“…The immune cells (B cells, T cells, dendritic cells and macrophages) of the rheumatoid pannus are believed to be involved in antigen presentation, antibody production and cytokine generation. An important role in antigen presentation has been identified for cathepsin S, which is involved in both the processing of endocytosed proteins to peptides suitable for presentation and the cleavage of the invariant chain to CLIP during MHC class II maturation (Riese et al, 1996;Shi et al, 1999;Villadangos et al, 1999). Studies of cathepsin S knockout mice revealed a decrease in their susceptibility to collagen-induced arthritis and impaired invariant chain processing in both dendritic cells and B cells (Nakagawa, Brissette et al, 1999).…”
Section: Synovium: Inflammation Hyperplasia Pannus Formation and Prmentioning
confidence: 99%